Punk Community in Criminology Study (Study in Ngaliyan District, Semarang City) - Millennia, Nurul Izzah; Anan, Yuni; Lestari, Indah; Arifin, Ridwan; Hidayat, Ashbar (Law Research Review Quarterly, 2020)
The purpose of this study was to find out what criminal cases were carried out by punk children, then what factors behind them committed the crime, and why they could enter the punk community. Punk kids are always associated with a negative action, look weird, steal, children are slang, immoral, and other negative things. Sometimes punk children choose to live on the road not only a factor in the conditions of economic difficulties, but also because they enjoy environmental conditions on the road, they feel their families do not care, and lack of education. Research methods The research method used in conducting research on the criminal acts of punk children community is to use qualitative research methods with a sociological juridical approach. Qualitative research methods according to Lexy J Moleong are research that intends to understand the phenomenon of what is understood by the subject of research, such as behavior, perceptions, motivations, actions, etc., holistically and in description in the form of words and language in a natural context. Data collection uses quantitative methods. The results of the study concluded that criminal acts or crimes by punk children were carried out due to economic, family, environmental factors, and lack of education.